PERFORMANCE ACCOUNTABILITY OF EDUCATION SERVICE BOLAANG MONGONDOW DISTRICT - Dilapanga, Abdul Rahman; Mantiri, Jeane (International Journal of Psychosocial Rehabilitation, 2020)
Clean governance is a demand for reform to optimize the achievement of national development goals. One indicator of clean governance is the implementation of a system of accountability for the administration of government tasks. This study aims to explore, analyze and interpret and provide a description of the Performance Accountability of the Education Office of Bolaang Mongondow Regency. The method or approach used in this study is a qualitative approach, in accordance with the formulation of the problem and research objectives which aim to reveal, analyze and interpret field data, therefore a qualitative approach is used. Analysis of the data used is an interactive model analysis of Miles and Huberman. Based on the results of research and discussion that has been described in the previous section, it can be concluded that: Performance Accountability of the Education Office of the Regency of Bolaang Mongondow has been accounted for through the performance reports of government agency performance (LAKIP) and has successfully implemented 6 (six) programs and 21 activities both funded through the APBD and APBN with an average achievement of 100%. These programs are lifted from three main themes of educational development, namely: 1) equity and expansion of access to education, 2) quality improvement, relevance, and competitiveness, and 3) governance, accountability and public imaging. Performance Accountability of the Office of Education is illustrated through: • Performance Achievement in the Expansion and Equalization of Access to Education, 2). Performance Achievement in Improving the Quality of Relevance and Competitiveness, 3). Performance on Strengthening Governance, Accountability and Public Imaging, 4). Program Output to Support the Expansion and Equitable Access to Education, 5). Program Output to Support Quality Improvement, Relevance and Competitiveness, 6). Program Output to Support Strengthening of Governance, Accountability and Public Imaging.